Has a Mono- or Bisegmental Lumbar Spinal Fusion Surgery an Influence on Self-Assessed Quality of Life, Trunk Range of Motion, and Gait Performance?. Issue 11 (1st June 2015) - Stief, Felix; Meurer, Andrea; Wienand, Johanna; Rauschmann, Michael; Rickert, Marcus
Abstract : Study Design: This investigation prospectively compared self-assessed quality of life and biomechanical measures of physical function before and after spinal fusion surgery in 26 adult patients with symptomatic lumbar degenerative disease. Objective: The objective was to demonstrate that (1) due to a reduction of low back pain, quality of life as well as gait parameters would improve after a spinal fusion surgery and (2) gait performance is more similar to that observed in healthy controls at the same age, whereas trunk range of motion remains unchanged after surgery. Summary of Background Data: Current outcome evaluations of spinal fusion surgery are based on radiological changes and self-report questionnaires. However, these traditional measures do not sufficiently assess the functionality. Methods: Twenty-six patients with a mean age of 59.3 (SD: 10.1) years and 20 healthy subjects at the same age were evaluated. Before and approximately 6 months after a mono- or bisegmental spinal fusion surgery, patients completed self-report questionnaires and biomechanical assessments of gait analysis and trunk range of motion in the 3 principal planes of the body. Results: Results indicated an improvement in quality of life as well as an increased pain-free walking distance, walking speed, step length, and maximum hip extension during the stance phase of gait. Anterior pelvis and thorax tilt were significantly reduced after the surgery without significant differences compared with the control group. Regarding the trunk range of motion, we observed a decrease in maximum forward flexion and an increase in the fingertip-floor distance after surgery. Conclusion: The study results show that lumbar spinal fusion is a useful procedure to improve patient's quality of life and gait performance. Although we performed only mono- and 2-level fusions, the sagittal alignment of the pelvis and thorax during walking was normalized. Clinical gait analysis contributes to the advancement of our knowledge regarding the functional changes after a spinal fusion surgery. Level of Evidence: 2 Abstract : Measures of physical function and outcome questionnaires were assessed before and approximately 6 months after spinal fusion surgery in 26 patients with symptomatic lumbar degenerative disease. There was an improvement in quality of life and gait performance, whereas forward flexion of the trunk decreased after surgery.